Ampliando os entrelaçamentos: uma análise historiográfica e topológica da gramática de Fernão de Oliveira e das Ordenações Manuelinas - Vilarinho, Ricardo Francisco Nogueira (2022)
In our theoretical and interdisciplinary research, we seek to prove our thesis that grammatical norms and legal norms have the same structure, which, according to Reale (2003), can be decomposed into Fact, Value and Norm. Following the Three-Dimensional Theory of Law, Miguel Reale (1910-2006), we seek to intertwine two distinct areas of knowledge, namely, Linguistic Historiography and History of Law. Regarding the methodology used, we rely on Bastos and Palma (2004) and their methodological proposal entitled História Interlaçada. Based on the interdisciplinary possibility proposed by the authors, we analyzed our corpora, Fernão de Oliveira's grammar, entitled Grammatica da Lingoagem Portuguesa, published in 1536 and Manuelinas Ordenações, code of Portuguese Law, first printed in 1514. for representing the normative three-dimensionality through the Borromean Knot, a topological figure composed of having closely related nodes, without overlapping one by the other. We emphasize that the use of Topology in the Human Sciences was opened by Jacques Lacan (1901-1981). Supported by Henry (1992) and his studies on the field of complementarity, especially in his reflections on the internal/external of linguistic theories and also supported by the values listed by Casagrande (2004), we analyzed our research objects. Regarding our hypothesis, we found that the grammatical and legal normative structure are the same, better saying, Fact, Value and Norm are present in the two texts studied. In this way, we also conclude that theoretical/methodological expansion is a possible option in historiographical studies, since interdisciplinarity is inherent in Linguistic Historiography, Bastos and Casagrande (2021), Batista (2014). Therefore, we believe that our reflections also contributed to the approximation of theories and methodologies from different areas that are now intertwined, highlighting possible points of intersection